A formação de professores a distância no Sistema UAB: análise de duas experiências em Minas Gerais - Juliana Cordeiro Soares Branco (2014)
Public policies concerning training for teachers appraise distance education as an strategy able to meet the educational demands of a country of such continental dimensions and diverse realities as Brazil. Under this perspective arises the Universidade Aberta do Brasil (Brazilian Open University) whose objective is to offer licentiates, initial training and continuing educational courses for teachers within the basic educational system. Thus, this research is about the limits and possibilities within the system UniversidadeAbertado Brasil regarding training for teachers, taking into account the role played by the organizational model of its face-to-face structures in the supporting poles in the participating cities as well as the organizing of the universities involved in this process. Moreover, it discusses the situation of the Open University System of Brazil highlighting its intellectual production on the theme; policies on distance education both in general, and in this specific system; the delineation of how the policies at the Open University of Brazil materializes in higher educational institutions; the infrastructure of the poles as well as its organizing of human resources and course materials. The empirical study was conducted in the undergraduate programs of the Federal University of Minas Gerais (UFMG) and the Federal University of Ouro Preto (UFOP), whose poles are the ones in the cities Conceição do Mato Dentro, Conselheiro Lafaiete and Governador Valadares, where interviews with course coordinators, and tutors were performed. A questionnaire was also administered to the students of the analyzed courses. The research was qualitative, and it involved both exploratory and comparative studies which allowed the verification of the different ways of implementing these policies. The results displayed that the Universidade Aberta do Brasils policies guide both the universities as well as the face-to-face supporting poles, nonetheless, each institution and each pole develop its own way of working according to their needs and possibilities, being the universities responsible for organizing the creation and implementation of courses. As a limitation of the creation and implementation of these training courses, it was reported the following problems: (1) there is a lack of face-to-face meetings during the courses, (2) there is an accumulation of tasks on the tutor when compared to the low payment and (3) there are low resources in its libraries. The research also showed that the face-to-face poles are better equipped and has better structure when the municipal management is involved with its development. There was evidence that such courses contribute to changing and improving the working practices, to the exchanging of experiences, and to providing access to new jobs and studying opportunities, in addition to improving the students reading and writing abilities, leading them to a more autonomous studying practice.